(x-4)(2x^2-7x+8)= 2x^3-8x^2-7x^2+28x+8x-32=2x^3-15x^2+36x-32

(x - 4)(2x

= (2x

= 2x

= 2x

_____

Zuzka23 distributed the terms the other way:

(x - 4)(2x

I personally find the continual switching between powers of x to be less easy to deal with when multiplying out the next step.

^{2}- 7x + 8) = x(2x^{2}- 7x + 8) - 4(2x^{2}- 7x + 8) (use distributive property)= (2x

^{3}- 7x^{2}+ 8x) + (-8x^{2}+ 28x - 32) (use distributive property again)= 2x

^{3}+ x^{2}(-7 - 8) + x(8 +28) - 32 (combine like terms)= 2x

^{3}- 15x^{2}+ 36x - 32_____

Zuzka23 distributed the terms the other way:

(x - 4)(2x

^{2}- 7x + 8) = 2x^{2}(x-4) -7x(x-4) +8(x-4)I personally find the continual switching between powers of x to be less easy to deal with when multiplying out the next step.